The Effectiveness of Using Advertisement to Improve Students’ Writing Skill - Rafida, Tien; Daulay, Sholihatul Hamidah; Nasution, Elsa Septriana Wijaya (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2023)
This research was conducted to analyze the effectiveness of using advertisements in improving students writing skills. The subject of this research was an English teacher and 26 students in X-MIPA class. To gather the data, the interview and questionnaire were conducted and the interview was done with the teacher the questionnaire was given to the students and then qualitatively analyzed. To analyze the data gotten, these steps were used; data reduction, data display, and conclusion. The study's conclusions showed that using advertisements in writing lessons helped students feel happy, enthusiastic, and motivated. However, some students had trouble expressing their thoughts in writing lessons due to a lack of vocabulary. The usage of advertisements in the classroom has helped students' writing abilities. Based on these findings, it is recommended that all teachers use advertising intensively in their teaching to further improve their students' writing skills.